2011
DOI: 10.1152/ajpheart.00356.2011
|View full text |Cite
|
Sign up to set email alerts
|

Maternal hypoxia alters matrix metalloproteinase expression patterns and causes cardiac remodeling in fetal and neonatal rats

Abstract: Tong W, Xue Q, Li Y, Zhang L. Maternal hypoxia alters matrix metalloproteinase expression patterns and causes cardiac remodeling in fetal and neonatal rats. Am J Physiol Heart Circ Physiol 301: H2113-H2121, 2011. First published August 19, 2011 doi:10.1152/ajpheart.00356.2011.-Fetal hypoxia leads to progressive cardiac remodeling in rat offspring. The present study tested the hypothesis that maternal hypoxia results in reprogramming of matrix metalloproteinase (MMP) expression patterns and fibrillar collagen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
55
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 51 publications
(77 reference statements)
7
55
1
4
Order By: Relevance
“…To determine whether potential mediators TIMP-3 and TIMP-4 were involved in the hypoxia-mediated downregulation of cardiomyocyte proliferation, the expression of TIMP-3 and TIMP-4 was measured by Western blot analysis. Consistent with the previous in vivo findings in fetal rat hearts of maternal hypoxia (38), ex vivo hypoxic treatment caused a significant increase in both TIMP-3 and TIMP-4 protein abundance, demonstrating a direct effect of hypoxia on the upregulation of TIMP-3 and TIMP-4 expression in fetal hearts (Fig. 3A).…”
Section: Hypoxia Increases P27 and Decreases Cyclin D2 Expressionsupporting
confidence: 91%
See 3 more Smart Citations
“…To determine whether potential mediators TIMP-3 and TIMP-4 were involved in the hypoxia-mediated downregulation of cardiomyocyte proliferation, the expression of TIMP-3 and TIMP-4 was measured by Western blot analysis. Consistent with the previous in vivo findings in fetal rat hearts of maternal hypoxia (38), ex vivo hypoxic treatment caused a significant increase in both TIMP-3 and TIMP-4 protein abundance, demonstrating a direct effect of hypoxia on the upregulation of TIMP-3 and TIMP-4 expression in fetal hearts (Fig. 3A).…”
Section: Hypoxia Increases P27 and Decreases Cyclin D2 Expressionsupporting
confidence: 91%
“…The long-term detrimental effects of fetal growth restriction on the development of cardiovascular disease in later adult life have been well established (2,3,10,23). Recent studies in a rat model of maternal hypoxia and fetal growth restriction demonstrated a decrease in cardiomyocyte proliferation and premature transition of mononucleated cells to binucleated cells with increased cell sizes in the fetal heart (1,38). In rat heart development, the transition of proliferative and hyperplasic growth of mononucleated cells to hypertrophic growth of binucleated cells and terminal differentiation of cardiomyocytes take place within the first 2 wk after birth (5).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…As such, offspring of preeclamptic pregnancies develop in an environment of placental insufficiency, restricted oxygen supply [28] and abnormal levels of circulating antiangiogenic factors in the mother [29]. Animal studies indicate exposure to hypoxia related to abnormal placental development results in elevated myocardial collagen [30]. This is consistent with findings in newborn pigs, whereby short-term exposure to hypoxemia led to sustained reductions in longitudinal peak systolic strain [31].…”
Section: Preeclampsiasupporting
confidence: 63%